Rare earths stick to rare cyanobacteria: Future potential for bioremediation and recovery of rare earth elements - Paper, Michael; Koch, Max; Jung, Patrick; Lakatos, Michael; Nilges, Tom; Brück, Thomas B. (Frontiers in Bioengineering and Biotechnology, 2023)
Biosorption of metal ions by phototrophic microorganisms is regarded as a sustainable and alternative method for bioremediation and metal recovery. In this study, 12 cyanobacterial strains, including 7 terrestrial and 5 aquatic cyanobacteria, covering a broad phylogenetic diversity were investigated for their potential application in the enrichment of Rare Earth Elements through biosorption. A screening for the maximum adsorption capacity of cerium, neodymium, terbium, and lanthanum was conducted in which Nostoc sp. 20.02 showed the highest adsorption capacity with 84.2 - 91.5 mg g-1. Additionally, Synechococcus elongatus UTEX 2973, Calothrix brevissima SAG 34.79, Desmonostoc muscorum 90.03, and Komarekiella sp. 89.12 were promising candidate strains, with maximum adsorption capacities of 69.5-83.4 mg g-1, 68.6-83.5 mg g-1, 44.7-70.6 mg g-1, and 47.2-67.1 mg g-1 respectively. Experiments with cerium on adsorption properties of the five highest metal adsorbing strains displayed fast adsorption kinetics and a strong influence of the pH value on metal uptake, with an optimum at pH 5 to 6. Studies on binding specificity with mixed-metal solutions strongly indicated an ion-exchange mechanism in which Na+, K+, Mg2+, and Ca2+ ions are replaced by other metal cations during the biosorption process. Depending on the cyanobacterial strain, FT-IR analysis indicated the involvement different functional groups like hydroxyl and carboxyl groups during the adsorption process. Overall, the application of cyanobacteria as biosorbent in bioremediation and recovery of Rare Earth Elements is a promising method for the development of an industrial process and has to be further optimized and adjusted regarding metal-containing wastewater and adsorption efficiency by cyanobacterial biomass.